2008
DOI: 10.1007/s12155-008-9011-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity in Switchgrass Collections Assessed by EST-SSR Markers

Abstract: Switchgrass (Panicum virgatum L.), is a warm season C 4 perennial grass, native to North American tall grass prairies. The high biomass production potential of switchgrass with low inputs makes it an excellent choice as a sustainable bioenergy crop. The objective of this study was to determine the genetic variability within and among 31 switchgrass populations obtained from Germplasm Resources Information Network (GRIN). Six plants from each population (186 genotypes) were characterized with 24 conserved grass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
93
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(113 citation statements)
references
References 45 publications
16
93
4
Order By: Relevance
“…These studies consistently illustrate significant differentiation between upland and lowland ecotypes, based on both nuclear DNA markers and cpDNA sequences (Cortese et al 2010;Gunter et al 1996;Missaoui et al 2006;Narasimhamoorthy et al 2008;Zalapa et al 2011). More recently, we showed the first case of clear genetic differentiation among switchgrass ploidy levels using molecular markers (Zalapa et al 2011).…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…These studies consistently illustrate significant differentiation between upland and lowland ecotypes, based on both nuclear DNA markers and cpDNA sequences (Cortese et al 2010;Gunter et al 1996;Missaoui et al 2006;Narasimhamoorthy et al 2008;Zalapa et al 2011). More recently, we showed the first case of clear genetic differentiation among switchgrass ploidy levels using molecular markers (Zalapa et al 2011).…”
mentioning
confidence: 55%
“…More recently, we showed the first case of clear genetic differentiation among switchgrass ploidy levels using molecular markers (Zalapa et al 2011). However, genetic studies showing geographic differentiation are lacking or inconsistent (Missaoui et al 2006;Narasimhamoorthy et al 2008;Cortese et al 2010).…”
mentioning
confidence: 99%
“…In a compensating allopolyploid, a chromosome from one of the subgenomes is replaced by its homoeologs so that the overall chromosome number remains unchanged. The DNA content of VS16 has been determined to be within the range expected for tetraploid switchgrass accessions [9] but, since no GISH or FISH have been performed on VS16, it is unknown whether this clone carries intersubgenome translocations. However, rearrangements and compensating aneuploidy in VS16 would likely lead to multivalent formation during meiosis resulting in tetrasomic inheritance of some markers.…”
Section: Linkage Mapsmentioning
confidence: 99%
“…Upland types are shorter, have finer leaves, and a slower growth rate than the lowland types and are adapted to the northern USA [1,4]. Lowland ecotypes are primarily tetraploid (2n=4x=36) while upland ecotypes can be tetraploid but are predominantly octoploid (2n=8x=72) [7][8][9]. Although lowland switchgrass had originally been considered an autotetraploid with a high degree of preferential pairing [10], genetic mapping has strongly suggested that it is a disomic tetraploid [11].…”
Section: Introductionmentioning
confidence: 99%
“…In nature, switchgrass plants with the same ploidy level can usually be easily intercrossed regardless of ecotype; however, hybrids between different ploidy levels are very rare [7,8]. Due to the ploidy barrier, genetic flow between upland and lowland ecotypes is limited, which has ultimately maintained a high level of genetic diversity in switchgrass germplasm [9][10][11][12][13][14]. Hybrid breeding, which has significantly impacted modern agriculture, is a method of creating new cultivars by crossing between genetic lines that have different backgrounds [15].…”
Section: Introductionmentioning
confidence: 99%